GENERALIZED MATRIXES OF GALOIS PROTOCOLS EXCHANGE ENCRYPTION KEYS - Beletsky А.Я. (Journal of Information Technologies in Education (ITE), 2016)
The methods of construction of matrix formation the secret protocols legalized subscribers of public communications networks encryption keys. Based key exchange protocols laid asymmetric cryptography algorithms. The solution involves the calculation of one-way functions and is based on the use of generalized Galois arrays of isomorphism relationship with forming elements, and depending on the selected irreducible polynomial generating matrix. A simple method for constructing generalized Galois matrix by the method of filling the diagonal. In order to eliminate the isomorphism of Galois arrays and their constituent elements, limiting the possibility of building one-way functions, Galois matrix subjected to similarity transformation carried out by means of permutation matrices. The variant of the organization of the algebraic attacks on encryption keys sharing protocols and discusses options for easing the consequences of an attack.